Prevalence and risk factors for keratoconus in a university-based population in Turkey. Issue 12 (December 2021) - Özalp, Onur; Atalay, Eray; Yıldırım, Nilgün
Abstract : The prevalence of KC in Turkey was 2.4%. Most subjects (78.6%) were unaware of their disease. Eye rubbing and consanguineous marriage were found as risk factors for KC occurrence. Abstract : Purpose: To determine the prevalence of keratoconus (KC) in the students and faculty members (aged ≥18 and ≤30 years) studying/working at the Medical and Health Sciences faculties of Eskişehir Osmangazi University. Setting: Eskişehir Osmangazi University, Eskişehir, Turkey. Design: Prevalence study. Methods: Subjects were randomly selected to undergo KC screening using a proportional stratified sampling method. Of the 648 invited subjects, 585 (90.3%) responded to the invitation. The demographic data, medical/family history, and habits of the subjects were collected using a standardized questionnaire. Subjects were classified as KC, ectasia susceptibility, and normal based on the corneal tomography. The chi-square and Kruskal-Wallis tests were used for the analysis of categorical variables and parametric values, respectively. Risk factors for KC were determined using logistic regression analysis. Results: Of the enrolled 585 subjects, the prevalence of KC was 2393/100 000 (2.4%, 95% CI: 1.3% to 4%), whereas that of ectasia susceptibility was 1538/100 000 (1.5%, 95% CI: 0.7% to 2.9%). Although the prevalence was much higher in males (4%, 95% CI: 1.7% to 7.7%) than in females (1.6%, 95% CI: 1.1% to 4.4%), the difference was not statistically significant ( P = .09). Most (78.6%, n = 11) patients with KC were unaware of their disease. Eye rubbing (odds ratio [OR]: 3.53, P = .024) and consanguineous marriage (OR: 12.87, P = .032) were independent risk factors for KC. Conclusions: To the authors' knowledge, this is the first population-based KC prevalence study in a randomized sample conducted in Turkey. The prevalence of KC in Turkey was much higher than in European countries but similar to neighboring countries in the Middle East. Eye rubbing and history of consanguineous marriage were significant risk factors.